2009
DOI: 10.1163/157180909x400204
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Quandaries about Genetic Data — A Comparative Perspective

Abstract: Recently, several regulatory initiatives have been taken by the Council of Europe, OECD and national legislators to regulate different aspects of human genetics. However, the latest research findings and the emergence of systems biology call this approach into question as they constitute a substantial change in natural science and philosophy. This article argues that law should take this paradigm shift into consideration and that it is not possible to perceive genetic data as exceptional and suitable for speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…This reconceptualiza- tion is important not only for the sake of theoretical clarity and to illuminate the full penumbra of interests in play; it serves to inform our policy, professional and legal responses to arguments about the need to recognize, and give effect to a right not to know. 4 Only by revealing the essential nature of what is at stake can we hope to turn any putative right into a reality.…”
Section: Introductionmentioning
confidence: 99%
“…This reconceptualiza- tion is important not only for the sake of theoretical clarity and to illuminate the full penumbra of interests in play; it serves to inform our policy, professional and legal responses to arguments about the need to recognize, and give effect to a right not to know. 4 Only by revealing the essential nature of what is at stake can we hope to turn any putative right into a reality.…”
Section: Introductionmentioning
confidence: 99%
“…Another study concluded that the definitions contained in guidelines produced by professional and advisory bodies and international organisations were very inclusive and reflected a broad understanding of genetic data (Krajewska 2009).…”
Section: Introductionmentioning
confidence: 99%
“…7 Thus, genetics and genomics appear not to have fulfilled many of their promises. I discuss this problem in legal terms in: Krajewska (2009a). 8 Of course, this is not to say that life sciences play no role in our every day life.…”
Section: Introductionmentioning
confidence: 99%
“…These difficulties translate into major conceptual quandaries about the regulation of the use of DNA and biological data. 8 I have analysed this problem in: Krajewska (2009b). New biotechnological devices and genetic diagnostic tools have been extensively used in medicine for years.…”
Section: Introductionmentioning
confidence: 99%